EVALUATING THE INFLUENCE OF DESTINATION BRAND EXPERIENCE ON TOURIST BEHAVIORAL INTENTION - Ramjit Singh; Nasiba Mehraj (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2019)
The main objective of this research was to study the impact of destination brand experience on tourist behavioral intention. Sample area of the study included four essential tourism destinations of the Kashmir valley, India viz: Gulmarg, Pahalgam, Sonamarg and the famous Boulevard Road. The convenient sampling method was applied for sampling purposes and total responses obtained were 385 out of 450.  SPSS 25.0 has been used to analyze data and study the overall impact of the destination brand experience on tourist's satisfaction and revisit intention. Several strategies are suggested that are based on the findings, like how to improve the different experiences. The results of the study demonstrate that tourists perceive a branded destination differently. The different kinds of experiences lead tourists dependent on destination. The different factors under brand experience that have been studied show how each factor contributes to tourists satisfaction and leads to their intentions in the future.